Foreign investments in Uganda's oil sector: Linkages and issues for the local economy - Anne Mette Kjær (Danish Institute for International Studies (DIIS), 2013)
The Ugandan economy resembles many other economies in sub-Saharan Africa in that it has a large subsistence sector, relies on a few primary commodities for export and depends on aid to finance its public services. Oil and minerals have so far not been important to the economy. However, this might change as an estimated 3.5 billion barrel oil reservoir has been discovered in Uganda's Western and Northwestern Albertine Graben. Minerals have also been found and are being sold off as concessions. If oil revenues start to be mobilized as currently planned (2016-17), significant changes in not only government finance but also in the governments' relationships with donors and in state–society relations are likely to occur. The consequences for local communities and the environment are also likely to be significant.
Keywords: 330